PENDIDIKAN PRANATAL DALAM PRESFEKTIF AL QUR’AN - Lilis Lilis; Kamil Kamil; Suriadi Suriadi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
The purpose of this study was to find out how the understanding and results of the application of prenatal education methods in the perspective of the Qur'an were in Sekuduk Village. This study uses a qualitative approach, descriptive method with the type of field research (field research), data collection techniques used in this study are observation, in-depth interviews and documentation. The technical analysis used is technical data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, the primary data in this study were 4 pregnant women, while the secondary data for husbands from wives were four. Based on the results of the study, it can be concluded that: 1) understanding of prenatal education in the Al-Qur'an perspective in Sekuduk Village, Sejangkung District, namely: There are still pregnant women in Sekuduk Village who do not understand prenatal education in the Al-Qr'an perspective, and there are also pregnant women who understand education by using the material for praying five times a day, listening to the holy verses of the Qur'an, multiplying reading the Qur'an, praying, and noble character. 2) Researchers found that there are still pregnant women who use the parental method first, with the old way that still believes in inanimate objects as helpers for children in the womb, and researchers also found that there are still pregnant women who understand in providing prenatal education in the perspective of the Qur'an, namely the speaking method, the method of including speech, the method of remembrance and prayer, the method of memorizing Al-qura'an, methods of playing and telling stories.